Doing more with more: Women on the board and firm employment - Tunyi Tunyi Abongeh (Journal of Business Research, 2023)
While corporations play a pivotal social role by creating employment opportunities, managers typically boost profitability during economic downturns by downsizing. Using a panel of US-listed firms from 2007–2016, we explore the impact of female representation on the board of directors (BOD) on firm-level employment. We find that firm-level employment increases while the likelihood of downsizing decreases with BOD female representation. In corroboration, the level of under-staffing, and hence its associated problems, reduces with BOD female representation. The impact of female directors on employment is stronger in the absence of tokenism, more evident during downturns and shaped by female director typology. Importantly, we find that, while over-staffing problems might emerge, overall employee productivity improves with female representation, suggesting that female directors do not sacrifice shareholder value in pursuit of employee interests. Overall, our results suggest that female directors are crucial in promoting employment in society.